Production of sanitary pads from banana stem fibres / Nur Syazana Abdul Halem ... [et al.] - Abdul Halem, Nur Syazana; Mohd Arbain, Maizatul Azween; Noryazid, Nor Ifa Syamira; Musa, Atiyyah (Universiti Teknologi MARA, Negeri Sembilan, 2023)
On average, women normally menstruate within a span of 7 to 15 days each month, which makes sanitary pads a necessary item for them. In 2018, sanitary pads held a majority share at 79% of the feminine hygiene market. However, they have taken over landfills as one of the most common wastes, and they take a long time to disintegrate. To address this issue, this project was initiated to create eco-friendly sanitary pads using banana stem waste, which is a byproduct of the harvest. The project aimed to determine the maximum absorption of liquid and wicking capacity of the pads from banana stem fibre, and then compare them with that of commercial brands. Four types of pads were produced, which vary by the number of layers. The results revealed that the pads made from four layers of banana fibre sheet had the highest wicking ability and absorbed up to 70 ml of liquid, comparable to the commercial pad, Libresse. Hence, it can be concluded that the ability of banana fibre sanitary pads to absorb liquid is proven to be equivalent to that of commercial pads. By further exploring this study, banana stem fibre sanitary pads could have the potential to replace traditional pads, reducing waste from used sanitary products and banana trees.